Analysis of Business Contribution of Plam Sugar to Farmers Income in Benua District South Konawe Regency - Febriani, Yayu; Abdullah, Weka Gusmiarty; Sadimantara, Fahria Nadiryati (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
This study aims to analyze the contribution of the palm sugar business to farmers' Income in Benua District, South Konawe Regency. This research was conducted in Benua District, South Konawe Regency. Where all respondent of the population is used as research samples. The variables in this study are total production costs, revenues, income palm sugar business, income other than palm sugar, farmers' total income, and income contribution. The analysis used is income analysis and contribution analysis, and the research results show that farmers' income from the palm sugar business has an average income of IDR1.579.727 per month. The contribution from the palm sugar business to total revenue is 43%. Meanwhile, 57% of farmers' income comes from non-palm sugar businesses, including cacao cultivation, patchouli, corn, pepper, and oil palm.